Hubungan Antara Activity Of Daily Living Dengan Kejadian Depresi Pada Lanjut Usia - Aliyah; Leya Indah Permatasari; Rizaluddin Akbar (Citra Delima Scientific journal of Citra Internasional Institute, 2025)
Elderly individuals undergo an aging process characterized by the accumulation of complex changes, particularly physical changes, which can affect their ability to perform activities of daily living (ADL). A decline in ADL abilities among the elderly can contribute to the onset of depression. This study aims to determine the relationship between ADL and the incidence of depression among elderly individuals in Sumber Village. This research employs a non-experimental quantitative design with a correlational approach using a cross-sectional method. The study involved a sample of 63 elderly individuals residing in Sumber Village, selected through simple random sampling. Data were collected using the Barthel Index questionnaire and the Geriatric Depression Scale (GDS), both of which had been validated and proven reliable. Data analysis was conducted using the chi-square test with a significance level of < 0.05. The results showed a significance value of 0.000 (0.000 < 0.05), indicating that the null hypothesis (Ho) was rejected. This finding suggests a significant relationship between ADL and the incidence of depression among the elderly in Sumber Village. Strengthening family support and motivation is essential to help optimize the elderly's abilities, minimize their dependency on others, and maintain their independence in performing activities of daily living.